Analisis Multimodal Representasi Ibu pada Feed Instagram @jokowi: Ibu Yang Berdaya (?) - Samuel Rihi Hadi Utomo (School of Communication Science and Media Business, 2023)
This research explores how the representation of mothers is articulated in the upload